Decentralization of public authority: European experience and action of Ukraine - Rosoliak, Oksana; Dyakovych, Olha (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article describes the experience of decentralization in the EU countries and analyzes the possibilities of its use in Ukraine. It is proved that one of the prerequisites for the decentralization of public power in the context of its democratship and maintenance of executive power is the recognition, legal regulation and the influence of the reform of the municipal self-government to the legal system of the state